Assessing the ecological and economic sustainability of energy crops - Hanegraaf, Marjoleine C; Biewinga, Edo E; van derBijl, Gert (Biomass & bioenergy, 1998)
The production and use of biomass for energy has both positive and negative impacts on the environment. The environmental impacts of energy crops should be clarified before political choices concerning energy crops are made. An important aid to policy-making would be a systematic methodology to assess the environmental sustainability of energy crops. So far, most studies on the environmental aspects of energy crops deal mainly with the energy production of the crops and the possible consequences for CO 2 mitigation. The Dutch Centre for Agriculture and Environment (CLM) has developed a systematic methodology to assess the ecological and socio-economic sustainability of biomass crops. The method is best described as a multicriteria analysis of process chains and is very much related to Life Cycle Assessment (LCA). Characteristics of our methodology are the use of: • definition of functional units; • analysis of the entire lifecycle; • definition of yield levels and corresponding agricultural practices; • analysis of both ecological and economic criteria; • definition of reference systems; • definition of procedures for normalisation and weighting. CLM has applied the method to assess the sustainability of ten potentially interesting energy crops in four European regions. The results are used to outline the perspectives for large scale production of biomass crops with regard to the medium and long term land availability in Europe. For the crops considered, net energy budget ranges from 85 GJ net avoided fossil energy per ha for rape seed for fuel to 248 GJ net avoided fossil energy per ha for silage maize for electricity from gasification. The methodology of the tool and its results were discussed at the concerted action “Environmental aspects of biomass production and routes for European energy supply” (AIR3-94-2455), organised by CLM in 1996. Major conclusions of the research: • Multicriteria analysis of process lifecycles is at present the best available option to assess the ecological and economical sustainability of energy crops. However, it is recognised that further research and development activities in the field of LCA are necessary. • Use of crops for generation of electricity is preferred to use of crops for transport fuels since the latter score low on both ecological and socio-economical criteria. • Large scale use and production of energy crops requires (a) choices and goals from agricultural, environmental, and energy policies, and (b) policy instruments for financial incentives e.g. with payments or with tax rebates, preferably per kilogram avoided CO 2 emission.